2011
DOI: 10.1088/0031-9155/56/11/006
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the oxygen enhancement ratio for ion beam radiation therapy

Abstract: The poor treatment prognosis for tumours with oxygen-deficient areas is usually attributed to the increased radioresistance of hypoxic cells. It can be expressed by the oxygen enhancement ratio (OER), which decreases with increasing linear energy transfer (LET) suggesting a potential clinical advantage of high-LET radiotherapy with heavy ion beams compared to low-LET photon or proton irradiation. The aim of this work is to review the experimental cell survival data from the literature and, based on them, to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
147
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(159 citation statements)
references
References 94 publications
10
147
0
Order By: Relevance
“…AA8 cells were slightly more radiosensitive compared to CHO cells under both oxic and hypoxic conditions, nevertheless, we found that the OER values at the 10% survival level (D 10 or LD 90 ) were similar for both CHO cells (2.68 6 0.15) and AA8 cells (2.76 6 0.08) ( Table 1). The OER values of approximately 3 are in concordance with other published studies and suggest that our hypoxic conditions were close to anoxic conditions used in other studies (15)(16)(17)(18)(19).…”
Section: Calculation Of the Maximum Protection By Dmso (Dmso Method)supporting
confidence: 92%
“…AA8 cells were slightly more radiosensitive compared to CHO cells under both oxic and hypoxic conditions, nevertheless, we found that the OER values at the 10% survival level (D 10 or LD 90 ) were similar for both CHO cells (2.68 6 0.15) and AA8 cells (2.76 6 0.08) ( Table 1). The OER values of approximately 3 are in concordance with other published studies and suggest that our hypoxic conditions were close to anoxic conditions used in other studies (15)(16)(17)(18)(19).…”
Section: Calculation Of the Maximum Protection By Dmso (Dmso Method)supporting
confidence: 92%
“…It is estimated that indirect effects of free radicals account for approximately two-thirds of the DNA damage caused by X-rays [48]. For high LET radiation, classic studies performed by Barendsen et al and others have shown an inverse relationship between OER and LET where effect of oxygen on cell radiosensitivity becomes diminished (OER = 1.0) for LET greater than 140 keV/”m [21,85] (Figure 2B). The main hypothesis for the decrease of OER with increasing LET is that high LET radiation predominately causes direct DNA damage (estimated at about 75% for alpha particle of 150 keV/”m [86]) independent of the free radical inflicted indirect DNA damage, thereby less affected by oxygen.…”
Section: Effect Of Cell Cycle and Oxygenationmentioning
confidence: 97%
“…In a clinical trial of high LET carbon ion beam, Nakano et al compared its efficacy against hypoxic and normoxic cervical tumors and showed similar disease-free survival between hypoxic (<20 mmHg) and oxygenated (>20 mmHg) tumors suggesting that high LET radiation can overcome the radioresistance caused by tumor hypoxia [90]. Modeling analysis, however, suggest that the reduction of OER with high LET radiation under the clinical tumor hypoxic environment (0.5-20 mmHg) is relatively moderate with approximately 15% benefit over photon [85]. Furthermore, the findings that patients with hypoxic tumors are associated with poor prognosis with treatments independent of oxygen status (such as surgery) suggest that hypoxic tumor could have a malignant phenotype as a result of colony selection under hypoxic condition which in turn is maintained by its fast consumption of O 2 .…”
Section: Effect Of Cell Cycle and Oxygenationmentioning
confidence: 99%
“…The surviving fraction SF (u) of each voxel is determined by the linear-quadratic model, which is an empirical formula for the predication of radiation response [14]:…”
Section: Sparse Dose Paintingmentioning
confidence: 99%